Gambaran Kadar Hematokrit pada Penderita Demam Berdarah Dengue di RSUD Al – Ihsan - Reza Ahmad Nazali; Agus Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Early signs of dengue virus infection are often nonspecific, which can result in delays in assessment. This disease can develop quickly, even in a matter of days or hours, and can result in serious conditions. The primary pathophysiology of dengue hemorrhagic fever (DHF) involves increased vascular permeability and impaired hemostasis. Increased blood vessel permeability can result in plasma leakage, hypovolemia, and even severe stress. Disturbances in hemostasis can result in thrombocytopenia and bleeding manifestations. In dengue fever sufferers, thrombocytopenia occurs due to antibodies attacking platelets, which make antigen-antibody complexes. Hematocrit levels can increase due to an increase in the number of blood cells or a decrease in the amount of plasma, which often occurs in cases of dengue fever. conversely, hematocrit levels can decrease due to an increase in plasma concentration, similar to the case of a decrease in the number of blood cells or anemia. Blood tests are very crucial in monitoring the patient's condition and determining the prognosis. Based on WHO testing guidelines, thrombocytopenia and plasma extravasation, which are reflected in blood concentrations, are crucial indicators in the assessment of dengue fever. The research method used in this research is narrative, carried out from March to May 2024 at Al-Ihsan Regional Hospital. The study population included 30 patients, and the sample was representative of the entire population. Research findings show that 24 out of 30 patients (80%) experienced an increase in hematocrit levels. Key terms: Dengue Hemorrhagic Fever, Hematocrit.